2017
DOI: 10.1128/aem.02956-16
|View full text |Cite
|
Sign up to set email alerts
|

Extraintestinal Pathogenic and Antimicrobial-Resistant Escherichia coli, Including Sequence Type 131 (ST131), from Retail Chicken Breasts in the United States in 2013

Abstract: Chicken meat products are hypothesized to be vehicles for transmitting antimicrobial-resistant and extraintestinal pathogenic Escherichia coli (ExPEC) to consumers. To reassess this hypothesis in the current era of heightened concerns about antimicrobial use in food animals, we analyzed 175 chicken-source E. coli isolates from a 2013 Consumer Reports national survey. Isolates were screened by PCR for ExPEC-defining virulence genes. The 25 ExPEC isolates (12% of 175) and a 2:1 randomly selected set of 50 non-Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 35 publications
(61 reference statements)
5
30
0
Order By: Relevance
“…Here, we found that the average virulence score was higher for strains isolated from shellfish in site 1 than in sites 2 and 3. Recently, Johnson et al (2017) assigned the ExPEC status to E. coli isolated from surface waters and animals based on the detection of a set of virulence genes. Their analysis focused on the detection of papAH and/or papC (encoding P fimbriae), sfa / focDE (S and F1 fimbriae), afa / draDC (Dr-binding adhesins), kpsMI (group 2 capsule) and iutA (aerobactin system); a strain being considered ExPEC when positive for at least two of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that the average virulence score was higher for strains isolated from shellfish in site 1 than in sites 2 and 3. Recently, Johnson et al (2017) assigned the ExPEC status to E. coli isolated from surface waters and animals based on the detection of a set of virulence genes. Their analysis focused on the detection of papAH and/or papC (encoding P fimbriae), sfa / focDE (S and F1 fimbriae), afa / draDC (Dr-binding adhesins), kpsMI (group 2 capsule) and iutA (aerobactin system); a strain being considered ExPEC when positive for at least two of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been reported that in Brazil, about 71.0% of the E. coli isolates from commercial chicken carcasses were MDR (Magiorakos et al, 2012); in Italy, 66.9% of the E. coli isolates from chicken meat were MDR (Ghodousi et al, 2015); in Egypt, 100% of the E. coli isolates from avian source were MDR (Enany et al, 2019), which demonstrated the high antimicrobial resistance. The addition of extensive subtherapeutic doses of antibiotics in animal feed is a very important reason for the rapid dissemination of antibioticresistant bacteria (Johnson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the infectious diseases associated with drug‐resistant bacteria, such as carbapenem‐resistant Enterobacteriaceae (CRE), cause serious morbidity, increased mortality, and lots of economic losses (de Kraker, Davey, & Grundmann, ). In addition to the extensive use of antibiotics in human disease treatment, antimicrobial consumption in global animal farming, especially extensively subtherapeutic‐dose addition in animal feed, is a very important reason for the rapid dissemination of antibiotic‐resistant Enterobacteriaceae (Johnson et al, ; Liu et al, ). Polymyxins have been regarded as a final line of antimicrobial agents against the serious infections caused by MDR bacteria, such as clinically CRE (Shen, Wu, et al, ).…”
Section: Introductionmentioning
confidence: 99%